PENGGUNAAN CANVA DALAM PEMBELAJARAN MENULIS TEKS NEGOSIASI SISWA KELAS X SMA NEGERI 1 PAMIJAHAN KAB. BOGOR - Prayoga Windya Buana; Stella Talitha; M. Ginanjar Ganeswara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the use of canva in learning to write negotiation textsfor class X students of SMA Negeri 1 Pamijahan Kab. Bogor. The method used inthis research is experimental method. The data collection techniques used weretests, questionnaires, and observations. The population in this study were X gradestudents of SMA Negeri 1 Pamijahan Kab. Bogor. The samples of this study wereclass X 5 as the experimental class and class X 9 as the control class using clusterrandom sampling technique. The first hypothesis, namely the use of canva canimprove negotiation writing skills in SMA Negeri 1 Pamijahan Kab. Bogor classstudents in writing negotiation texts, was tested, as evidenced by the pretest dataobtained in the experimental class by obtaining the class average score, which was58.13 at the mastery level of less able. For the average post-test score of theexperimental class, 85.43 is at the very capable mastery level. Then, it can also beseen from the calculation of the mean obtained the price of tcount = 3.01 and theresults of d.b 58 with the ttable level t0.99 = 2.39 and t0.95 = 1.67. Thus the tcountis greater than the ttable, namely 1.67 < 3.01 > 2.39. The second hypothesis can betested, proven by the existence of student constraints from the results ofquestionnaire analysis as many as 12 or 40% of respondents experienced problemspouring ideas or thoughts. Then 9 or 30% of respondents experienced problemscomposing and analyzing sentences in writing negotiation texts. Furthermore, 10 or33% of respondents experienced problems using canva multimedia. Thus, it can beconcluded that the use of canva can improve negotiation text writing skills in classX students of SMA Negeri 1 Pamijahan Kab. Bogor.